Aliada : an online platform matching maids with customers in Mexico - Lee, Angela Y.; Funston, Vasilia Kilibarda (London : Kellogg School of Management, 2017)
This case puts students in the shoes of Mexican entrepreneur Rodolfo Corcuera of the tech startup Aliada, an online platform that matches maids with customers in Mexico City. With backing from one of Mexico City's newest venture capital firms, Corcuera's business now needs to scale, and he is considering how best to position his offering to those on whom his business model depends--maids and customers. To tackle this, students will learn about basic concepts from psychology that can inform marketers. More specifically, they will learn how basic human needs (nurturance, security) fuel self-regulatory goals (promotion and prevention goals, respectively), which in turn impact how people approach their consumption goals. Students will analyze Aliada's current Facebook ads, watch videos of some of Aliada's current maids and customers to assess whether they seem more motivated by promotion or prevention goals, and recommend optimal messaging for Facebook ads and subway banners in order for Corcuera to be most appealing to these two target audiences who may have different motivations.
Originally Published InLee, A. Y., & Funston, V. K. (2017). Aliada: An online platform matching maids with customers in Mexico. 5-217-250. Evanston, IL: Kellogg School of Management at Northwestern University.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Corcuera, Rodolfo; Aliad -- Management -- Case studies; Facebook (Firm) -- Case studies; Women household employees -- Mexico -- Mexico City -- Marketing -- Case studies; Internet advertising -- Mexico -- Mexico City -- Psychological aspects -- Case studies; Consumers -- Attitudes -- Case studies; New business enterprises -- Mexico -- Mexico City -- Case studies